We must not forget : Holocaust stories of survival and resistance - Hopkinson, Deborah (Scholastic Focus, 2021)
Collects stories and recollections from Holocaust survivors, together with black and white photographs and newspaper clippings. Lets the voices of these survivors speak for themselves as they speak to the persecution they faced and the resistance they took part in against the Nazis.